Level of follicular fluid vitamin D and embryo quality in a sample of Iraqi women undergoing IVF - Alawad, Zainab M. (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Vitamin D has been linked to fertility since its receptors were found in reproductive organs. Nevertheless, its exact role in fertility is yet to be cleared. Objectives: To analyze follicular fluid (FF) vitamin D in females doing Intracytoplasmic Sperm Injection (ICSI), to compare its level between Polycystic Ovary Syndrome (PCOS) and non-PCOS females, and to explore whether vitamin D correlates with oocytes number, percentage of oocyte maturity, fertilization rate and percentage of high quality embryos. Patients and methods: This comparative observational study was done, from January to October 2018, at Al Amal IVF Center, Jenin hospital, Baghdad. The study was conducted on 40 women; 18 had PCOS, 15 had blocked fallopian tubes and 7 had idiopathic infertility. FF vitamin D was analyzed by Ichroma kit, Boditech. Deficient, insufficient, and sufficient vitamin D levels were as: <10, 10-29, and 30-100 ng/ml, respectively. Results: Most participants were deficient (12 women) or insufficient (18 women) of vitamin D, only 10 women had adequate vitamin D levels. FF vitamin D was higher in non-PCOS than PCOS women (P= 0.011). The correlation between vitamin D and oocytes number was not significant. However, it was significant with percentage of oocyte maturity (rho= 0.459, P= 0.003), fertilization rate (rho= 0.471, P= 0.002) and percentage of high quality embryos (rho= 0.316, P= 0.047). Conclusions: PCOS patients, when compared to non-PCOS, have lower vitamin D levels. FF vitamin D might correlate with percentage of oocyte maturity, fertilization rate and percentage of high quality embryos in patients undergoing ICSI.